Tingkat Efisiensi Perbankan Syariah Pasca Spin Off dengan Metode Two-Stage Data Envelopment Analysis - Sallsa Khairunnisa (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
This study aims to determine the level of efficiency of Islamic banks after the spin off during the period of 2011-2016. To measure the performance, Two-Stage Data Analysis Envelopment (DEA) is used. The first step of this method is measuring efficiency performance of Islamic banks using DEA method with CRS assumption. The second step estimating factors affecting the efficiency performance using Tobit regression model. The determination of input and output variables in this study uses intermediation approaches. Input variable consists of Fix assets, Third Party Fund (DPK) and Operating Expenses, while the output variable consists of Total financing and Operating Income. The results of the research shows the level of efficiency of BNI Syariah during the 2011-2016 period is still not efficient with 99%, while the level of efficiency of BJB Syariah from 2011 to 2016 is 98%. The result of Tobit regression model showed that Total assets and ROA has a positive and significant to the level of efficiency of BNI Syariah , while the coefficient of FDR and NPF are not significant influence. Furthermore, that influence the level of efficiency of BJB Syariah is total assets, while the coefficient of ROA, FDR and NPF are not significant influence.